2018
DOI: 10.1108/jadee-11-2016-0077
|View full text |Cite
|
Sign up to set email alerts
|

Chinese consumers’ willingness to pay for rice

Abstract: Purpose China’s expanded rice imports offer a profitable business opportunity for both domestic and international grain marketers. The purpose of this paper is to analyze the impact of select variables on Chinese consumers’ rice choices, specifically focusing on country-of-origin, price, organic, brand, freshness, and taste. The study concludes with suggestions for domestic and international rice marketers to help them develop more efficient rice marketing plans. Design/methodology/approach This study develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
3
18
0
2
Order By: Relevance
“…Xu, Su, and Lone [11] also found that price is a major determinant of the willingness of Chinese consumers to pay for organic foods. The results of the study support the premise that low food expense consumers are attracted to brands of rice that are affordable, hence low willingness to pay for organic foods.…”
Section: Resultsmentioning
confidence: 99%
“…Xu, Su, and Lone [11] also found that price is a major determinant of the willingness of Chinese consumers to pay for organic foods. The results of the study support the premise that low food expense consumers are attracted to brands of rice that are affordable, hence low willingness to pay for organic foods.…”
Section: Resultsmentioning
confidence: 99%
“…En primer lugar, ese resultado responde a la necesidad de China de satisfacer la demanda por variedad de alimentos de la población. Reflejo de ello es el alza del consumo de variedades de arroz provenientes de Vietnam, Camboya, Pakistán y Tailandia, que compiten con los cultivadores chinos en precio, calidad y seguridad (Xu, Su y Lone., 2018). La última es sumamente relevante, ya que las importaciones fueron estimuladas, además, por la preocupación social que generaron los escándalos por la producción de arroz tóxico (H. .…”
Section: El Acaparamiento De Tierras Para La Producción De Arrozunclassified
“…Entre 2007 y 2014, estos se duplicaron (H. , lo que perjudicó a los consumidores de menores ingresos. Esto incentivó las importaciones de arroz de menor calidad de Laos, India y Camboya (Xu, Su y Lone, 2018). En adición, es probable que el alza de los costos de producción, la competencia de cultivos y la escasez de agua aumenten el atractivo del arroz importado (Bandumula, 2017).…”
Section: El Acaparamiento De Tierras Para La Producción De Arrozunclassified
“…Thus, it is found that the labor cost of EA is about 3.6 times that of CA. Regarding the cash inflow, the rice yield for CA was 7500 kg/ ha and the average price of CA was about 5 CNY/kg for several years [31]; thus, the economic benefits of CA is 21,000 CNY (3.75 CNY/m 2 ) with NPV amounting to 2.98 CNY/m 2 . The rice yield of EA was 3700 kg/ha, but the price is 26 CNY/kg, which is five times higher than CA.…”
Section: Economic Benefit Assessmentmentioning
confidence: 99%
“…Since the land rent in EA accounted for 66% of the cost (12,600 CNY or 3 CNY/m 2 ), if the farmland is managed without rent fee as CA, the net economic benefits of EA will significantly increase. The cash inflow was characterized as economic benefits received and ecosystem services provided, in which the rice price is the most important factor due to the fact that Chinese consumers are price sensitive in their rice purchases [31]. Meanwhile, rice price is also highly correlated to the scale of rice cultivation and sales [31,47].…”
Section: Economic Benefits Of the Small-scale Paddies In The Mountainmentioning
confidence: 99%